O canto de anúncio como caráter diagnóstico de linhagens de Dendropsophus microcephalus (Anura: Hylidae) na sua área de distribuição geográfica - Bautista, Danny Josue Ordoñez (2023)
Reproductive isolation can be studied considering different approaches, including postzygotic and pre-zygotic reproductive isolation. The advertisement calls in frogs acts as a prezygotic factor in reproductive isolation and is important for taxonomic purposes, mainly due to its importance in specific recognition and mate choice. Studies on advertisement call variation have been crucial for understanding the evolution of mating signals and for describing new species of anurans. The objective was to analyze the use of the advertisement call as a tool for recognizing the lineages of Dendropsophus microcephalus. I analyzed 117 recordings from different locations from Mexico to Brazil were analyzed. The calls were obtained from calls libraries: Macaulay Library, The Cornell Lab of Ornithology; Jacques Vielliard Neotropical Phonoteca; Laboratory of Taxonomy and Systematics of Neotropical Anurans; Amphibian Phonoteca-UNAM and the Ixchel group Centro América. The primary and secondary notes of the calls were analyzed independently. The calls variables analyzed were call duration (DC), number of notes (NN), note duration (DN), pulse per note (PN), note interval (IEN), note repetition rate (TRN), pulse frequency (FP), and dominant frequency (FD). Calls were assigned to each lineage according to the distributions determined by Dr. W. Duellman (1970): D. m. underwoodi (from Mexico to Costa Rica), D. m. microcephalus (from Costa Rica to Colombia), D. m. misera (Venezuela to the Amazon basin) and the corners of central Brazil were considered as D. m. ssp. Calls considered "outliers" were removed from the analyses. The advertisement call of the lineages D. m. microcephalus, D. m. misera and D. m. underwoodi has the same basic structure, starting with a primary note, followed by several biphasic secondary notes that can have up to seventeen notes. In D. m. ssp the biphasic notes are not appreciated, moreover, most acoustic variables of the advertisement call have difference between the lineages, except for the FDs of the secondary notes. In the PCAs the variables with the greatest influence overall were DC, DN, (primary and secondary), and FD (primary and secondary). The lineages D. m. microcephalus, D. m. underwoodi and some individuals of D. m. misera are grouped at opposite endpoint of PC1 in relation to individuals of D. m. ssp. with distribution in central Brazil. We also found a positive relationship between PC1 and PC3 between the latitudinal clines, therefore, the variables increase from south to north. Our results show that populations of D. m. misera from Brazil and the individuals from D. m. ssp differ in structure and vocalization properties in relation to the other lineages. This difference in vocalization could indicate that populations from Brazil are reproductively isolated from the other lineages of D. microcephalus; suggesting that populations from Brazil are a different species from D. microcephalus. Further analysis with an integrative taxonomic approach is needed to determine the taxonomic status of populations from Brazil.